The Muse at Play : Riddles and Wordplay in Greek and Latin Poetry - Kwapisz, Jan; Petrain, David; Szymański, Mikołaj (Beiträge zur Altertumskunde, 2013)
Riddles and other word games are widespread in classical literature and played a crucial role in shaping Greek and Roman cultural discourses, yet few efforts have been made to treat them in all their variety and complexity. This volume, the fruit of a conference held in May 2011 by the Institute of Classical Studies of the University of Warsaw, gathers contributions on a range of topics linked by the theme of linguistic play. With its broad spectrum of approaches, the book serves as companion to a fascinating but somewhat neglected area of ancient culture - the domain of the Playful Muse.